Digital work in the transport sector: in search of the employer. (1st December 2018) - Antonio Loffredo; Marco Tufo
Abstract : This article analyses two of the major digital platforms dealing with transport: Uber and FlixBus. It reconstructs the nature of these platforms as transportation companies and studies their structures. It finds that such companies can assume 'trilateral' or 'quadrilateral' structures, depending on the subjects involved, with different consequences for labour relations. Following on from this, the article investigates the applicability of labour law in such structures, searching for an employment relationship in 'trilateral' structures and identifying the real employer in 'quadrilateral' structures.